Congenital Fibrosis of Extraocular Muscles: A Systematic Review and Meta-Analysis. Issue 2 (3rd April 2023) - Van Swol, Joshua M.; Myers, Walter K.; Nguyen, Shaun A.; Wilson, M. Edward
ABSTRACT: Purpose: To quantify typical disease characteristics for patients with congenital fibrosis of the extraocular muscles (CFEOM) including pre-and post-surgical ocular alignment and head positioning as well as average improvement with surgical intervention. Patients and Methods: This investigation is a systematic review and meta-analysis. All studies detailing surgical intervention in cohorts of individuals with CFEOM were included. Ocular alignment and head positioning before and after surgery was recorded. Meta-analyses were performed to quantify these findings along with other patient characteristics across all included studies. Results: The estimated average improvement in vertical alignment for patients with unilateral and bilateral CFEOM was 34.8 pd (prism diopters) and 21.27 pd, respectively. For horizontal alignment, patients with unilateral and bilateral CFEOM improved an average of 25.39 pd and 10.99 pd after surgery, respectively. There was no significant difference between the two most common surgeries used to address hypotropia and blepharoptosis in this patient population. The estimated proportion of patients with post-surgical head alignment within 5–9° was 60.64% and was 28.25% for patients with<5° of alignment. Conclusion: This study was able to illuminate many characteristic features of patients with CFEOM. Surgical intervention for the ocular alignment and head positioning of these patients demonstrates promising utility.